2011
DOI: 10.1186/1754-1611-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Production of lentiviral vectors with enhanced efficiency to target dendritic cells by attenuating mannosidase activity of mammalian cells

Abstract: BackgroundDendritic cells (DCs) are antigen-presenting immune cells that interact with T cells and have been widely studied for vaccine applications. To achieve this, DCs can be manipulated by lentiviral vectors (LVs) to express antigens to stimulate the desired antigen-specific T cell response, which gives this approach great potential to fight diseases such as cancers, HIV, and autoimmune diseases. Previously we showed that LVs enveloped with an engineered Sindbis virus glycoprotein (SVGmu) could target DCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…As demonstrated from our previous study, addition of 1-deoxymannojirimycin (DMJ) into cell culture during vector production can yield vectors with improved capability to transduce DCs (Tai et al 2011). This was accomplished by increasing the amount of high-mannose structures present on viral envelope glycoproteins through DMJ-mediated inhibition of class I α(1,2)-mannosidase activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated from our previous study, addition of 1-deoxymannojirimycin (DMJ) into cell culture during vector production can yield vectors with improved capability to transduce DCs (Tai et al 2011). This was accomplished by increasing the amount of high-mannose structures present on viral envelope glycoproteins through DMJ-mediated inhibition of class I α(1,2)-mannosidase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that DMJ could enhance the efficiency of SVGmu-bearing LVs for transduction of DCs by increasing the amount of high-mannose structures present on SVGmu through the inhibition of cellular mannosidase activity (Tai et al 2011). In this study, we found that the DC-LVs produced by LV-MGFP with DMJ resulted in a 9-fold increase in transduction of 293T.hDCSIGN cells and 2-fold enhancement in GFP-specific CD8 + T cell response compared to vectors produced without DMJ.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of such systems include a reduced requirement for samples and reagents, fast and high-throughput results, low power consumption, a reduced contamination risk and a high degree of parallelization [1,3]. These designs take advantage of the great developments occurring in microfabrication techniques.…”
Section: Lab-on-a-chip (Loc)mentioning
confidence: 99%
“…Various diagnostic techniques have been employed to effectively integrate multiple microfluidic components into fully automated LOC systems that can perform sophisticated biomedical analyses [2]. Specifically, capillary driven microfluidics, multilayer soft lithography, multiphase microfluidics, electrowetting-on-dielectric mechanisms, electrokinetics, and centrifugal microfluidics are the platforms with the most potential for incorporating microfluidics into a variety of biomedical engineering applications [3]. Each approach has unique advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples are the detection of rat IgG from a hybridoma cell culture by Lai et al [17], the detection of Dengue non-structural protein 1 (NS-1) by Yusoff et al [29], the implementation of a 5-step ELISA through a simple 2-layer design by Ibrahim et al [15], the detection of a cytokine interferon-gamma by He et al [14], plasma separation and detection of Hepatitis B virus by Lee et al [18], and allergen screening by Chen et al [5]. Recent developments have also introduced various enhancements to the basic CD valve design such as suction-enhanced siphon valve by Gorkin et al [13], semi-circular valve by Lin et al [21], ice valve by Amasia et al [2], thermally actuated elastomer valve by Pitchaimani et al [27], wax valves by Lee et al [18] and Abi-Samra et al [1], and dissolvable film valve by Gorkin et al [12]. …”
Section: Introductionmentioning
confidence: 99%